Web Portal Pemasaran Telur Ayam - Ikhwan Fauzy Djuhu; Muhammad Rifai Katili; Sitti Suhada (Gorontalo State University, 2021)
Currently, the consumption demand for eggs is always higher than the level of egg production, but there are are still few markets that provide marketing service for the sale of farming products such as eggs. In addition, chicken egg stcok itself is difficult to find manually and has impact on its relatively high price. This study aims to build a web portal for chiken egg marketing, especially chicken farmers in Pilohayanga village, in terms of marketing web-based chicken egg to support business activites and MySQL databases. The finding indicates that the application off the chiken egg marketing system by using a web application can simplify the process of marketing or purchasing chicken eggs online.